Enhanced visible light photocatalytic performances of self-assembled hierarchically structured BiVO4/Bi2WO6 heterojunction composites with different morphologies. Issue 57 (31st May 2016) - Chen, Long; Meng, Dawei; Wu, Xiuling; Wang, Anqi; Wang, Junxia; Yu, Meihua; Liang, Yujun
Abstract : A possible mechanism for enhanced photocatalytic activity over self-assembled hierarchical BiVO4 /Bi2 WO6 composites was proposed according to calculated energy band positions. Abstract : Novel self-assembled hierarchical BiVO4 /Bi2 WO6 heterostructured composites with different morphologies were controllably synthesized via a facile and template-free solvothermal method. The effects of the molar ratio of V to W on the structure, morphology, photocatalytic activity and photoelectrochemical properties of the BiVO4 /Bi2 WO6 composite photocatalysts were investigated in detail. The results showed that all the BiVO4 /Bi2 WO6 composites exhibited much better photocatalytic activities for methylene blue (MB) degradation and photoelectrochemical performances than pure BiVO4 and Bi2 WO6 . Among the composites, the BiVO4 /Bi2 WO6 microsphere with the molar ratio of V to W of 2 : 1 exhibited the best photocatalytic performance. The mechanism of enhanced activity was systematically investigated by UV-vis diffuse reflectance spectroscopy (DRS), photoluminescence (PL) spectroscopy, and photo-electrochemical methods including transient photocurrent responses, electrochemical impedance spectroscopy (EIS) and Mott–Schottky plots. The enhanced photocatalytic activity could be ascribed to the tetragonal–monoclinic heterophase structure, high surface oxygen vacancy concentration, narrow band gap energy and mainly the formed heterojunction structure which could effectively promote the separation of photogenerated electron–hole pairs. In addition, a possible photocatalytic mechanism for the enhanced photocatalytic activity was proposed on the basis of the calculated energy band positions of BiVO4 and Bi2 WO6 .